An assessment of neoliberal coups: the 1973 chilean military coup and the 1980 Turkish military coup - ÖKTEN, NİLAY; BALCI, MERAL (My University, 2022)
The article attempts to identify the changes caused by military coups, one of the means of spreading neoliberal ideology, on the political economy of countries and discusses the place of the US hegemony in this context. The influence of armies on the political economy of countries is examined based on the examples of the Chilean military coup of 1973 and the Turkish military coup of 1980, and the place of the army element in the histories of these countries is discussed. Even if a hegemon power has enough economic, military and political power to intervene directly, it can use less costly and more legitimate tools for indirect intervention than a direct one. The policy of instrumentalizing local military forces and exporting neoliberalism to countries, which the US hegemony preferred to apply in the Cold War era and generally in the last quarter of the 20th century, is clearly seen in the examples of Chile and Turkey. Therefore, the main topic of this study is the use of armies as a tool by the neoliberal hegemon USA, and it argues that the military coups of Chile and Turkey were indirect foreign interventions, and that they were the products of the US hegemony as events that served to declare the victory of neoliberalism.
Keywords: Neoliberalism; US Hegemony; Chile; Turkey; Military Coups